Fischerei und fischereibiologische Untersuchungen im Nordost-Atlantik im 1. Halbjahr 1996 - Schöne, Rüdiger (1996)
Biological investigations were carried out onboard the commercial freezing trawler "KIEL" off the Norwegian coast in February/March and in the Bear Island area in May 1996. Data will be used as German contribution to the assessmentsof the ICES "Arctie Fisheries Working Group". Informations about the fishery and the concentrations of cod, haddock, saithe and redfish in the areas between Röst-, Nordvest-,Fuglöy-Bank and Bear Island are given. Length - and age distributions as well as preliminary results of stomach- and gonad investigations are represented. Johann Heinrich von Thünen-Institut, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010